PELAKSANAAN LAYANAN DASAR BIMBINGAN DALAM MEMBENTUK KARAKTER SISWA DI SD MUHAMMADIYAH PROGRAM KHUSUS KOTA SURAKARTA - Minsih, Minsih Minsih (Universitas Muhammadiyah Surakarta, 2015)
This study aims to look at the implementation process of the teacher class guidance in buildingthe character of students. This study is a qualitative research with phenomenological approachnaturalistic. Phenomenological approach seeks to understand human behavior in terms of aframework of thinking and acting people themselves. Implementation of comprehensive guidanceservices done by classroom teacher and teacher assistant in SD Muhammadiyah Surakarta SpecialProgram was very inô€ƒ€ uential on the formation of student character. The process of comprehensiveguidance services form the basis of guidance services, response service, individual planning services,and support systems. This study focuses on basic counseling services and individualized service.This guidance service is a companion program for all students under the guidance of psychologistsand counselors. The basic service is a service provided for all students in order to achieve optimalprocess of self development through activities classically presented systematically. This serviceis also aimed at preventing the emergence of problems in the educational process at school.